Integrating Succession and Gender Issues from the Perspective of the Daughter of Family Enterprise: A Cross-National Investigation - Constantinidis, Christina; Nelson, Teresa (Management international / Gestiòn Internacional / International Management)

(untitled) (HEC Montréal et Université Paris Dauphine, 2009)
AbstractWe engage a gender analysis, including consideration of the social phenomena of separation and hierarchy, to consider the role, condition and aspirations of daughters of family enterprise as they consider the option of family entrepreneurship. From this perspective we examine the extant literature and present findings from two exploratory empirical research efforts, one in Belgium and one in the U.S., to better understand internationally how daughters perceive their leadership paths in the family business. We take into consideration growing social acceptance of women’s leadership, and women’s own career-mindedness, which influence traditional views of the opportunities for daughters inside and outside of the family business. Research avenues and practical recommendations to support successful succession of daughters are discussed.